Thyroid Diseases After Total Knee Replacement: A Multi-center, Propensity-score-matched Cohort Study - LI, CHEN-PI; LO, SHAO-WEI; HSU, CHRISTINE; LI, YUN-FENG; TSAI, RU-YIN; CHANG, HUI-CHIN; GAU, SHUO-YAN (In vivo (Athens), 2024)
Thyroid diseases are prevalent endocrine disorders that significantly affect overall health. Although the impact of pre-existing thyroid dysfunction on total knee replacement (TKR) outcomes has been studied, the potential for TKR to increase the risk of developing thyroid disorders remains unexplored. We examined electronic medical records from a large U.S. research network in the TriNetX research network. The study focused on patients with osteoarthritis, comparing those who had total knee replacement surgery (TKR) between 2005 and 2018 to a non-TKR group who did not have the surgery. Propensity score matching was employed to control for critical confounders. The hazard ratios (HRs) for the risk of thyroid diseases in TKR patients versus non-TKR controls were assessed. Post-matching, the TKR cohort demonstrated a significantly higher risk of developing thyroid diseases compared to the non-TKR cohort (unadjusted HR=1.218, 95%CI=1.169-1.269). This elevated risk persisted after adjusting for confounders (adjusted HR=1.126, 95%CI=1.061-1.196). Stratification analysis indicated that female TKR patients and those aged ≥65 years were at higher risk of developing thyroid diseases than their respective control groups. This study suggests a potential link between TKR and an increased risk of thyroid diseases, particularly among older adults and females. Potential mechanisms include inflammatory processes, surgical stress, autoimmune responses, and pharmacological effects. Healthcare providers should be vigilant in monitoring and managing thyroid dysfunction in TKR patients. Further research is necessary to elucidate the underlying mechanisms and develop preventive strategies.